(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Company rule in India refers to the rule or dominion of the British East IndiaCompany on the Indian subcontinent. This is variously taken to havecommenced in 1757, after the Battle of Plassey, when the Nawab ofBengal Sirajuddaulah surrendered his dominions to the Company in1765, when the Company was granted the diwani,or the right to collect revenue, in Bengal and Bihar or in1773, when the Company established a capital in Calcutta, appointed itsfirst Governor-General, Warren Hastings, and became directly involvedin governance.